Cover Image. (28th April 2020) - Xu, Shichen; Pan, Jie; Cheng, Xian; Zheng, Jiangxia; Wang, Xiaowen; Guan, Haixia; Yu, Huixin; Bao, Jiandong; Zhang, Li
Abstract : The cover image is based on the Research Article Diallyl Trisulfide, a H2S donor, inhibits cell growth of human papillary thyroid carcinoma KTC‐1 cells through a positive feedback loop between H2S and cystathionine‐gamma‐lyase by Shichen Xu et al., https://doi.org/10.1002/ptr.6586 .